Religious Life between Symbolic Power, Sacred Space, Political Thought, and Knowledge Production - Busro Busro (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2026)
This editorial note introduces Vol. 10 No. 1 (2026) of Religious: Jurnal Studi Agama-Agama dan Lintas Budaya by situating its five articles within a shared narrative on religious life across diverse social, political, spatial, aesthetic, and academic contexts. The issue brings together five original research articles authored by eight scholars from six countries: Cameroon, Portugal, Bulgaria, Russia, Indonesia, and Turkey. The articles collectively explore religious extremism and symbolic domination, sacred space and contemplative atmosphere, illuminative ontology and political thought, Orthodox hymnography and iconography, and the production of knowledge within Religious Studies. This editorial note argues that religion should not be understood only as doctrine, ritual, or institutional affiliation, but also as a symbolic force, spatial experience, political imagination, aesthetic expression, and academic practice. By reading the articles through the themes of symbolic power, sacred space, political thought, and knowledge production, this issue contributes to the development of Religious Studies through interdisciplinary and cross-cultural perspectives. It opens further discussion on how religion shapes collective life across regions, traditions, and scholarly formations.